Rescue of Pressure Overload‐Induced Heart Failure by Estrogen Therapy. Issue 1 (January 2016) - Iorga, Andrea; Li, Jingyuan; Sharma, Salil; Umar, Soban; Bopassa, Jean C.; Nadadur, Rangarajan D.; Centala, Alexander; Ren, Shuxun; Saito, Tomoaki; Toro, Ligia; Wang, Yibin; Stefani, Enrico; et al.
Abstract : Background: Estrogen pretreatment has been shown to attenuate the development of heart hypertrophy, but it is not known whether estrogen could also rescue heart failure (HF). Furthermore, the heart has all the machinery to locally biosynthesize estrogen via aromatase, but the role of local cardiac estrogen synthesis in HF has not yet been studied. Here we hypothesized that cardiac estrogen is reduced in HF and examined whether exogenous estrogen therapy can rescue HF. Methods and Results: HF was induced by transaortic constriction in mice, and once mice reached an ejection fraction (EF) of ≈35%, they were treated with estrogen for 10 days. Cardiac structure and function, angiogenesis, and fibrosis were assessed, and estrogen was measured in plasma and in heart. Cardiac estrogen concentrations (6.18±1.12 pg/160 mg heart in HF versus 17.79±1.28 pg/mL in control) and aromatase transcripts (0.19±0.04, normalized to control, P <0.05) were significantly reduced in HF. Estrogen therapy increased cardiac estrogen 3‐fold and restored aromatase transcripts. Estrogen also rescued HF by restoring ejection fraction to 53.1±1.3% ( P <0.001) and improving cardiac hemodynamics both in male and female mice. Estrogen therapy stimulated angiogenesis as capillary density increased from 0.66±0.07 in HF to 2.83±0.14 ( P <0.001, normalized to control) and reversed the fibrotic scarring observed in HF (45.5±2.8% in HF versus 5.3±1.0%, P <0.001). Stimulation of angiogenesis by estrogen seems to be one of the key mechanisms, since in the presence of an angiogenesis inhibitor estrogen failed to rescue HF (ejection fraction=29.3±2.1%, P <0.001 versus E2). Conclusions: Estrogen rescues pre‐existing HF by restoring cardiac estrogen and aromatase, stimulating angiogenesis, and suppressing fibrosis.